PROFILING PESERTA DIDIK UNTUK PERENCANAAN PEMBELAJARAN EFEKTIF PESERTA DIDIK KELAS III DI SDN 3 ANCARAN - Salwa Regina Anggraini; Riqi Taufikurohman; Seli Selvia; Ilah Nurlaelah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Understanding student characteristics is a critical foundation for effective instructional planning, yet it remains underimplemented in many elementary school classrooms. This study aims to describe the student profiling process and its application in designing effective learning for Grade III students at SDN 3 Ancaran, Kuningan Regency. A qualitative descriptive approach was employed. Data were gathered through classroom observation, semi-structured interviews with the class teacher, and document analysis. Subjects consisted of one class teacher and 20 Grade III A students. Data analysis followed the Miles and Huberman interactive model, comprising data reduction, data display, and conclusion drawing. Validity was ensured through source and technique triangulation. Findings show that Grade III A students exhibit diverse profiles: (1) learning readiness varies from sufficient to very good; (2) learning styles are predominantly audio-visual (75%), with 25% showing kinesthetic preferences; (3) academic abilities span three levels—high, developing, and emerging; (4) interests cluster around visual arts, sports, and digital games; and (5) socio-emotional development is generally adequate to good, with some students needing support in self-confidence and social skills. These profiles directly shaped the teacher’s differentiated strategies, including varied media use, flexible grouping, and tiered tasks. Despite some implementation challenges such as limited time and unstandardized instruments, the teacher effectively utilized profiling data in lesson planning. This study concludes that systematic student profiling is essential for responsive, student-centered learning aligned with the Merdeka Curriculum.